2009
DOI: 10.1007/s00018-009-8796-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine regulatory peptide-1 and −2: Novel bioactive peptides processed from VGF

Abstract: Neuroendocrine regulatory peptides (NERP)-1 and NERP-2 are derived from distinct regions of VGF, a neurosecretory protein that was originally identified as a product of a nerve growth factor-responsive gene in rat PC12 cells. The amino acid length of human NERP-1 is 26, and that of rat NERP-1 is 25. Human and rat NERP-2 are both 38 amino acid peptides. NERPs colocalize with vasopressin in the storage granules of the paraventricular and supraoptic nuclei in the hypothalamus of both rats and humans. Administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 51 publications
(59 reference statements)
0
13
0
1
Order By: Relevance
“…VGF peptides are present in endocrine cells early during development and adulthood and VGF increases in hyperplasia and tumors [41]. Different peptide fragments have been proposed to derive from VGF, including NAPP, NERP, TLQP, AQEE, and LQEQ [40, 52, 53]. We detected seven peptides of VGF protein, four of them derived from previously described regions: R.LLQQGLAQVEAGR.R (NERP-1), K.NAPPEPVPPPR.A (NAPP-129), R.HHPDLEAQAR.R (TLQP-62/30), and R.SQEEAPGHR.R (APGH).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VGF peptides are present in endocrine cells early during development and adulthood and VGF increases in hyperplasia and tumors [41]. Different peptide fragments have been proposed to derive from VGF, including NAPP, NERP, TLQP, AQEE, and LQEQ [40, 52, 53]. We detected seven peptides of VGF protein, four of them derived from previously described regions: R.LLQQGLAQVEAGR.R (NERP-1), K.NAPPEPVPPPR.A (NAPP-129), R.HHPDLEAQAR.R (TLQP-62/30), and R.SQEEAPGHR.R (APGH).…”
Section: Discussionmentioning
confidence: 99%
“…Remaining three polypeptides (R.SPQPPPPAPAR.D (509–519) , R.ELQETQQER.E (353–661) , and K.LHLPADDVVSIIEEVEEK.R (466–483) ) are derived from regions without known biological activity. Biological roles of VGF-derived peptides like regulation of energy balance, food intake, body fluid homeostasis, and reproduction were described [4, 5, 13, 23, 45, 52]. Clinical and preclinical data links VGF-derived peptides in models of human depression (TLQP 62) [49], neuropathic and inflammatory pain (TLQP 21, AQEE 30) [10, 42], amyotrophic lateral sclerosis, Parkinson’s, and Alzheimer’s diseases [6, 37].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, to our knowledge, studies on the neurosecretory activity of this family have been limited so far to the demonstration of the ability of NERPs to suppress hypertonic saline-or angiotensin II-induced vasopressin release from hypothalamus and the pituitary (40). In addition, specific analyses have suggested that neither VGF nor TLQP-21 has an impact on the growth hormone-IGF-I axis in pigs or mice (3,32).…”
mentioning
confidence: 99%
“…The role of the VGF peptides in neurons containing TH, parvoalbumin, GAD and somatostatin remains to be investigated; however the major hypothesized role is that VGF peptides could act as neuromodulators. The VGF role as neuromodulator has already been reported for certain VGF peptides, for instance NERPs regulate vasopressin secretion (Toshinai and Nakazato, 2009; D’Amato et al, 2012), TLQP-21 increases FSH release from the pituitary (Aguilar et al, 2013), TLQP-62 regulates hippocampal synaptic activity (Thakker-Varia et al, 2007, 2010; Bozdagi et al, 2008; Lin et al, 2015). …”
Section: Discussionmentioning
confidence: 89%